Predicate model presentation indirect link between the procedure in business processes - Голян, Наталья Викторовна; Голян, Вера Вволодимиривна; Пелешенко, Светлана Сергеевна (Eastern-European Journal of Enterprise Technologies, 2012)
The models of the generalized construction of implicit choice between the procedures of business processes in the form of logical networks are constructed. In the future, the resulting model will provide the possibility of constructing the logical network design to identify implicitly the choice and evaluation of the results